ANTIMICROBIAL RESISTANCE AND GUIDELINE RECOMMENDATIONS: CONTEXTUALIZATION AND ADAPTABILITY - Stalteri, Rosa (My University, 2020)
BACKGROUND: Antibiotics are essential medicines and their effectiveness is under threat due to antimicrobial resistance. Guidelines are one way to conserve antibiotic effectiveness given that they are intended to modify clinician prescribing. Guidelines that provide antibiotic recommendations should make explicit contextual considerations that influence antimicrobial resistance and their downstream effects on resistance emergence. METHODS: We conducted a systematic review of tuberculosis, gonorrhoea, and respiratory tract infection guidelines and recommendations to examine how and to what extent they are considering contextual factors that influence antimicrobial resistance. We also investigated whether there are guidelines and recommendations that can be adopted or adapted to local contexts. RESULTS: We found that within 74 included guidelines, two thirds of recommendations considered antimicrobial resistance. Of which only five guidelines considered all factors required to consider local aspects such as values, resource use, acceptability, feasibility, and equity. As such, these five guidelines can be either adopted or adapted to Canadian and other contexts. We also found that 39% of guidelines met credibility scores of 60% or greater in AGREE II domains: scope and purpose, rigor of development, and editorial independence. CLINCAL IMPLICATIONS: There are very few Infectious disease guidelines for highly prevalent diseases that do not consider all important contextual factors may influence antimicrobial resistance. Our findings can support societies and organizations, public health policy, and health care stakeholders to develop and implement guidelines that are applicable to local contexts efficiently and resourcefully. Our antimicrobial resistance recommendation framework, used in addition to GRADE Evidence to Decision frameworks, is a start to having this come to fruition.
Keywords: Guidelines; Recommendations; Antimicrobial resistance; Contextual